Upaya Dalam Menanam Karakter Percaya Diri Melalui Kegiatan Class Meeting Pada Anak Usia Dini Di Kelompok B PAUD Mandiri Tegalsari Pekon Kutadalom Kecamatan Gisting Kabupaten Tanggamus Lampung - Risyka Diniarza (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
This research model uses a PTK approach by taking Kemmis and Mc model. Taggart. This type of research is research collaborative classroom action between researchers and classroom teachers. Subject on This research is the group B children of Pembina Kindergarten, Bantul District totaling 24 children, namely 14 girls, 10 boys, who are vulnerable 5-6 years old. The object of research is self-confidence. In this research Researchers used observation and documentation methods in collecting data. Data analysis techniques were carried out descriptively qualitatively and quantitatively. The research results showed that active play activities were carried out in 2 cycles it can increase children's self-confidence. Improved taste This self-confidence can be seen from the results of the observation data obtained each cycle increases. Before the action completes the feeling of confidence 2 children (8.33%) had not yet developed criteria, 14 were starting to develop children (58.3%), developed according to the expectations of 7 children (29.17%), and criteria developing very well, there was only 1 child (4.17%). In cycle I, completeness The child's self-confidence increases to underdeveloped criteria by 0 child(0%). 6 children (25%) began to develop according to the development criteria hope for 12 children (50%) and 6 children (25%) are developing very well. On cycle II experienced an increase in the criteria for not yet developing 0 children (0%), starting 1 child developed (4.17%), according to the criteria for developing according to expectations there were 10 children (41.67%) and developed very well there were 13 children (54.17%) so learning can be said to be successful because there were 23 children (95.84%) out of 24 The number of group B children in the Pembina Kindergarten, Bantul District has reached indicator of success. This research was stopped until cycle II because it had already been completed meet the success indicator criteria.